Exploring the Determinants of Export Performance of Indian Pharmaceutical Industry - A Quantile Regression Approach - Rentala, Satyanarayana; Byram, Anand (Journal of Contemporary Research in Management (JCRM), 2015)
Examining determinants of export performance is a widely researched stream of international business. Many researchers across the world have attempted to investigate the various determinants of export performance in various research settings. Majority of the previous studies that examined the determinants of export performance have been undertaken in the context of developed economies. The main objective of this research is to understand the determinants of export performance in the context of Indian pharmaceutical industry. Quantile regression method, which was rarely used in the earlier studies, has been employed to analyze the findings of this research. Export sales have been considered as the dependent variable and the independent variables considered for the study are size of the firm (measured as sales), research and development expenses, profitability, age, advertising expenses, capital intensity, import of raw materials and import of capital goods. The research presents an analysis of firms belonging to 147 pharmaceutical firms operating in India for the period 2000-2013. The analysis is presented using OLS regression method and further to that, quantile regression method was employed to understand the impact of various determinants of export performance for pharmaceutical firms in India. The findings of this research indicate that six out of the eight independent variables considered for the study have a significant impact on the export performance of Indian pharmaceutical firms.